Effectiveness of Ethno-STEM Based Chimistry to Improve Students Critical Thinking Skills - Hiqmah, Noor; Rienovita, Ellina; Al-Latief, Imam Shofwan; Sholehuddin, Sholehuddin; Santosa, Tomi Apra (Postgraduate, University of Mataram, 2023)
Ethno-STEM based chemistry learning has a significant impact on students' knowledge and competencies. However, ethno-STEM based chemistry learning experiences many problems in its application and several issues that need to be clarified. This research aims to determine the effectiveness of ethno-STEM based chemistry learning in improving students' critical thinking skills. This type of research is meta-analysis. This meta-analysis synthesizes 19 articles consisting of 1021 participants published in 2018-2023. The research results show that ethno-STEM based chemistry learning has a big influence on students' critical thinking skills (Hedges'g = 0.915; p < 0.001). Research can provide important information in ethno-STEM-based chemistry learning in schools.